The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.coviro.2020.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Roles of small RNAs in the establishment of tolerant interaction between plants and viruses

Abstract: In a tolerant plant-virus interaction, viral multiplication is sustained without substantial effects on plant growth or reproduction. Such interactions are, in natural environments, frequent and sometimes even beneficial for both interactors. Here we compiled evidence showing that small RNAs modulate plant immune responses and growth, hence adjusting its physiology to enable a tolerant interaction. Importantly, the role of small RNAs in tolerant interactions resembles that required for establishment of a mutua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Growing evidence shows that the host‐encoded miRNAs could modulate virus replication and pathogenesis (Khan et al, 2020 ; Tribolet et al, 2020 ; Wong et al, 2020 ; Zhang et al, 2020 ; Zheng et al, 2020 ). miRNAs through binding with viral RNA interact with different species or strain of viruses (Križnik et al, 2020 ; Trobaugh & Klimstra, 2017 ). miRNAs by binding to the 3′‐UTR (El‐Nabi et al, 2020 ; Liu et al, 2017 ) or 5′‐UTR of viral RNA play an important role in COVID‐19‐host interplay and viral replication (Demirci & Adan, 2020 ; Nersisyan et al, 2020 ).…”
Section: The Potential Function Of Mirnas Following Covid‐19 Infectionmentioning
confidence: 99%
“…Growing evidence shows that the host‐encoded miRNAs could modulate virus replication and pathogenesis (Khan et al, 2020 ; Tribolet et al, 2020 ; Wong et al, 2020 ; Zhang et al, 2020 ; Zheng et al, 2020 ). miRNAs through binding with viral RNA interact with different species or strain of viruses (Križnik et al, 2020 ; Trobaugh & Klimstra, 2017 ). miRNAs by binding to the 3′‐UTR (El‐Nabi et al, 2020 ; Liu et al, 2017 ) or 5′‐UTR of viral RNA play an important role in COVID‐19‐host interplay and viral replication (Demirci & Adan, 2020 ; Nersisyan et al, 2020 ).…”
Section: The Potential Function Of Mirnas Following Covid‐19 Infectionmentioning
confidence: 99%
“…We reported the top hits of these searches in Supplemental Files S1 and S4 to provide a link between the potato genome online resources and NCBI resources to facilitate comparative analyses between the potato genes/proteins with other organisms. Analyses of small RNAs including 21-and 24-nt small RNAs and miRNAs from the same time points indicate similarities to tolerant infections in other potato cultivars, expanding upon and further solidifying the results of the few other studies that have examined small RNAs in PVY-infected potato [73,74,102]. Tolerant plants may serve as viral reservoirs that may produce recombinant viruses and/or outbreaks and, therefore, tolerance to PVY infection is not a useful trait for potato breeders.…”
Section: Discussionmentioning
confidence: 76%
“…Importantly, Russet Burbank plants in this study were largely asymptomatic and did not display any chlorosis or strong mosaic symptoms. Since PVY reached high levels of systemic infection without obvious phenotypic effects on the plants, infections in this study could be categorized as tolerant [ 13 , 73 , 74 , 75 ]. This description is also congruent with the gene expression changes observed in this study (i.e., lower expression of defense genes and higher expression of genes involved in photosynthesis and chloroplast function).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, miR156 overexpression increased drought stress tolerance. In turn, Križnik et al (2020) [26] suggested that miR156 in Nicotianas can participate in plant resistance to viral infection. The targets of miR159 are MYB genes [82], which are transcription factor genes that control different processes, including responses to biotic and abiotic stress, as well as plant tolerance to metal stress [83,84].…”
Section: Effect Of Fe 3 O 4 Nanoparticles On Barley Mirna Expressionmentioning
confidence: 99%
“…Furthermore, miR159c is known to be involved in the response to fungal infection in wheat [25]. However, miR156 can be involved in resistance to viral infection [26]. According to Yao et al (2021) [27], miR156 and miR159 families' targets are at least three genes that are related to the resistance of Tibetan hulless barley against fungal diseases, such as barley leaf stripe [27].…”
Section: Introductionmentioning
confidence: 99%